Statistical Literacy of Senior High School Students in Problem-Solving with AKM Model Data Content and Uncertainty in Terms of Mathematical Ability - Rohmah, Nur; Fuad, Yusuf; Ekawati, Rooselyna (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2024)
This study investigates the statistical literacy of high school students in solving AKM model problems on data content and uncertainty. The research involved 36 students from eleven X classes at SMA Negeri 1 Taman Sidoarjo, each with high, medium, and low mathematical abilities. The study used mathematics ability tests and AKM model problem solving tests validated by two mathematics education lecturers and senior mathematics teachers. The results showed that high mathematics ability students met all indicators of statistical literacy, including understanding statistical data, presenting statistical data, and presenting the result of data processing. Students with moderate mathematics ability only fulfilled two indicators, understanding and presenting statistical data. Students with low mathematics ability struggled with understanding data, presenting data, and providing arguments related to statistical concepts. The study concluded that high mathematics ability students met all indicators of statistical literacy, while medium mathematics ability students could only determine answers through peer discussion and could not provide suitable arguments. Students with low mathematics ability struggled to understand the characteristics of the presented statistical data.